Avoided Mortality Associated with Improved Air Quality from an Increase in Renewable Energy in the Spanish Transport Sector: Use of Biofuels and the Adoption of the Electric Car - Ana R. Gamarra; Yolanda Lechón; Marta G. Vivanco; Mark Richard Theobald; Carmen Lago; Eugenio Sánchez; José Luis Santiago; Juan Luis Garrido; Fernando Martín; Victoria Gil; Alejandro Rodríguez-Sánchez (Atmosphere, 2021)
This paper assesses the health impact, in terms of the reduction of premature deaths associated with changes in air pollutant exposure, resulting from double-aim strategies for reducing emissions of greenhouse gases and air pollutants from the transport sector for the year 2030 in Spain. The impact on air quality of selected measures for reducing emissions from the transport sector (increased penetration of biofuel and electric car use) was assessed by air quality modeling. The estimation of population exposure to NO2, particulate matter (PM) and O3 allows for estimation of associated mortality and external costs in comparison with the baseline scenario with no measures. The results show that the penetration of the electric vehicle provided the largest benefits, even when the emissions due to the additional electricity demand were considered.